1976
DOI: 10.1111/j.1476-5381.1976.tb07664.x
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE CONCERNING THE INVOLVEMENT OF 5‐HYDROXYTRYPTAMINE IN THE LOCOMOTOR ACTIVITY PRODUCED BY AMPHETAMINE OR TRANYLCYPROMINE PLUS l‐DOPA

Abstract: I Pretreatment of rats with p-chlorophenylalanine (PCPA; 2 x 200 mg/kg) decreased the concentration of 5-hydroxytryptamine (5-HT) in the brain. It also decreased the locomotor activity produced by tranylcypromine plus L-DOPA administration 24 h after the second dose of PCPA. 2 Pretreatment with p-chloroamphetamine, which produced a similar decrease in brain 5-HT concentrations did not decrease the locomotor response to tranylcypromine and L-DOPA. 3 PCPA pretreatment decreased the rise in the concentration of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…The effect of depleting brain 5-hydroxytryptamine with p-chloroamphetamine on the behaviour produced by tranylcypromine and L-DOPA The original findings of Green & Kelly (1976) were confirmed and it was observed that all the behavioural changes such as forepaw treading and head weaving were still present in animals pretreated with p-chloroamphetamine (Figure 3). Furthermore these changes were still present 90 min after L-DOPA administration and did not diminish as might be expected if residual 5-HT were being further depleted.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The effect of depleting brain 5-hydroxytryptamine with p-chloroamphetamine on the behaviour produced by tranylcypromine and L-DOPA The original findings of Green & Kelly (1976) were confirmed and it was observed that all the behavioural changes such as forepaw treading and head weaving were still present in animals pretreated with p-chloroamphetamine (Figure 3). Furthermore these changes were still present 90 min after L-DOPA administration and did not diminish as might be expected if residual 5-HT were being further depleted.…”
Section: Resultssupporting
confidence: 61%
“…Consequently the activity counts were increased although produced by a radically different behaviour in the methysergide and methergoline pretreated rats. Administration of either p-chloroamphetamine or tranylcypromine and tryptamine results in the appearance of syndromes indistinguishable from those seen after tranylcypromine and L-tryptophan and there is evidence that these syndromes also result from release of brain 5-hydroxytryptaminergic systems (Foldes & Costa, 1975;Jacobs, 1976;Green & Kelly, 1976). These syndromes were affected by Lesioning of the spinal cord 5-HT tracts by discrete injection of 5,7-DHT resulted in an enhanced behavioural response to the 5-HT agonist, 5-MeODMT, which is consistent with the view of Jacobs & Klemfuss (1975) that the syndrome is predominantly mediated by spinal 5-HT systems and with other evidence that 5-HT receptors become supersensitive on denervation (Trulson et al, 1976;Hole, Fuxe & Johnson, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To do this, both biochemical measurements and a behavioural model have been used in an analagous way to the previous study on 5-HT. The behaviour studied was that of the locomotor activity which follows administration of an MAO inhibitor and L-3,4-dihydroxyphenylalanine (L-DOPA) and which has been shown to be the result of increasing dopamine concentrations in the brain (Everett, Wiegland & Rinaldi, 1963;Everett, 1966;Green & Kelly, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural changes following the L-DOPA administration were exactly as described by Green & Kelly (1976).…”
Section: Introductionmentioning
confidence: 99%